Den unge Grundtvig og Norge - Albeck, Gustav (Grundtvig-Studier, 1985)
The Young Grundtvig and Norway By Gustav Albeck This article is a revised and extended version of the lecture given by Professor Albeck on April 30th 1984 at the annual general meeting of the Grundtvig Society in Oslo. It describes Grundtvig’s close relationship to a number of Norwegian friends he made during his residence at the Walkendorf hostel in Copenhagen in the years 1808-11; this circle of friends lasted and widened to include other Norwegians in his later life. Grundtvig was 67 before he set foot on Norwegian soil, but from his early youth he had familiarised himself with the Norwegian landscape and history through Norwegian literature. His feeling of kinship with the spirit and history of Norway was for a time stronger than his consciousness of being Danish. In his youth Norway and the Norwegians played a major role in opinion-making in Denmark, and in this respect Grundtvig was no different from his contemporary Danes. But the idea of Norway’s future continued to concern him long after his youth was over. The lecture, however, confines itself to the way certain Norwegians regarded Grundtvig between 1808 and 1811. When Grundtvig returned to Copenhagen from Langeland in 1808 he had no friends in the capital. But at the Walkendorf hostel he met first and foremost Svend B. Hersleb, a Norwegian theologian, to whom he addressed a jocular poem in the same year, revealing that Grundtvig now felt himself young again and among young people following his unrequited passion for Constance Leth. Otherwise we have only a few witnesses to this first period of happiness, with Grundtvig gaining a foothold on the Danish parnassus through his first Norse Mythology and Scenes from Heroic Life in the North. The fullest accounts of Grundtvig’s relationship to the Norwegians in the period following his nervous breakdown and religious breakthrough in 1810 come from the journals of the Norwegian-Danish dean and poet, Frederik Schmidt, made during various trips to Denmark. These journals were published in extenso between 1966 and 1985 in three volumes, the last of which includes a commentary by the editors and a postscript by Gustav Albeck. Many of the valuable notes about Grundtvig are repeated in the lecture. Frederik Schmidt was the son of a Norwegian bishop; he became a rural dean and later a member of the first National Assembly at Eids voll in 1814. He was a Norwegian patriot but loyal to the Danes and in fact returned to Denmark in 1820. His descriptions of Grundtvig’s conversations with Niels Treschow, the Norwegian-born Professor of Philosophy at Copenhagen University, give an authentic and concentrated picture of Grundtvig’s reflections on his conversion to a strict Lutheran faith, which for a time threatened to hinder his development as a secular writer. Schmidt found their way of presenting their differing views “very interesting and human”, and Grundtvig’s Christian faith “warm, intense and sincere”. “In the animated features of his dark eyes and pale face there is something passionate yet also gentle”. When Schmidt himself talked to Grundtvig about a current paper which stated that in early Christianity there was a fusion between Greek thought and oriental feeling, Grundtvig exclaimed, “Yet another Christianity without Christ!” A draft of a reply to one of Schmidt’s articles shows that at that point, April 1811, Grundtvig did not believe in the working of “the living word” in its secular meaning. The draft was not printed and Grundtvig does not appear to have discussed it with Schmidt. There is a very precise description of Grundtvig’s appearance: “There is... something confused in his eyes; he sometimes closes them after a tiring conversation, as if he wants to pull his thoughts together again.” Schmidt in no way agrees with Grundtvig’s point of view, which he partly puts down to “disappointed hopes, humbled pride and the persecution... he has been subjected to...” But he does find another important explanation in Grundtvig’s “need for reassuring knowledge” and his conviction “that the misery of the age can only be helped by true religious feeling”. There are also descriptions of Grundtvig in a more jovial mood, for example together with Professor George Sverdrup, where Grundtvig repeated some rather unflattering accounts of the playwright Holberg’s behaviour towards a couple of professors who were colleagues. The same evening he and Schmidt set about attacking Napoleon while Treschow and Sverdrup defended him. Schmidt considered Grundtvig’s little book, New Year’s Eve, “devout to the point of pietist sentiment”, but thought the error lay rather in Grundtvig’s head than his heart. Lovely is the Clear Blue Night (Dejlig er den himmel blaa), published in April 1811 was even read aloud by Schmidt to a woman poet; but he criticised The Anholt-Campaign. After 1814 Schmidt adopted a somewhat cooler tone towards Grundtvig’s books. He was unable to go along with Grundtvig’s talk of a united Denmark- Norway as his fatherland. He criticised the poems Grundtvig published in his periodical, Danevirke, including even The Easter Lily for its “vulgar language”, which Grundtvig appeared to confuse with a true “language of power”. It is impossible to prove any close relationship between Schmidt and Grundtvig, but he was an attentive observer when they met in Copenhagen in 1811. With the opening of the Royal Frederik University in Christiania in 1813 Grundtvig became separated from his Norwegian friends, as Hersleb, Treschow and Sverdrup were all appointed to the new Norwegian university. They were keen for Grundtvig to join them as Professor of History. Sverdrup in particular was captivated by his personality, and in a letter dated April 21st 1812 he informed Grundtvig that he was among the candidates for the post proposed by the commission to the King. But Grundtvig himself hesitated; he felt “calm and quietly happy” in Udby “as minister for simple Christians”. To his friend, the Norwegian-born Poul Dons, he wrote, “... something in me draws me up there, something keeps me down here.” The fact that he never got the job was in many ways his own fault. His World Chronicle (1812) could not but offend scholars of a rationalist approach, in particular the prediction at the end of the book about the new university’s effect. It is linked to Grundtvig’s interpretation (1810) of the letters to the seven churches in Revelation, which are seen as a prediction of the seven great churches in the historical advance of Christianity. “It was an idea,” says Albeck, “which in spite of its obvious irrationality never left Grundtvig, and as late as 1860 it found poetic form in the great poem, The Pleiades of Christendom (Christenhedens Syvstjerne).” Grundtvig “was in no doubt that the sixth church was the Nordic, and that it would grow out of the Norwegian university, the new Wittenberg.” In 1810 Grundtvig felt himself “chosen to be the forerunner of a new reformer, a new Johan Huss before a new Luther.” From a scholarly point of view there is no reason to reproach the Danish selection panel for the negative judgment they reached regarding Grundtvig’s qualifications as a historian. His name was not even mentioned in the appointments for the new professorships. He had caused quite a stir not long before by writing a birthday poem for the King in which he directly expressed his wish that the new university might become a Wittenberg. The poem took the form of a series of accusations against Norway and the Norwegians, and in particular against Nicolai Wergeland, who in a prize-winning essay on the Norwegian university entitled Mnemosyne had stuck a few needles into Denmark and the Danes. Grundtvig accused the Norwegians of ingratitude to Denmark and unchristian pride. Even his good friend Hersleb reacted to such an attack. From the diaries of the Norwegian, Claus Pavels, we know how the Norwegian poet, Jonas Rein, wrote and told Grundtvig that “a greater meekness towards people with a different opinion would be more fitting for a teacher of Christianity.” Grundtvig replied that he had had to speak the truth loud and clear in a degenerate age. The Bishop of Bergen, Nordal Brun, also considered Grundtvig’s views as expressed to the King “misplaced and insulting”. He was particularly hurt that Norway “should have to thank Denmark for its Christianity and protestantism”. When Grundtvig printed the poem in Little Songs (Kv.dlinger) in 1815, Nicolai Wergeland was moved to write Denmark’s Political Crimes against the Kingdom of Norway, published in 1816. For Grundtvig’s Norwegian friends it was a matter of regret that he did not come to Norway, not least for Stener Stenersen, who in 1814 became a lecturer and in 1818 a professor of theology at the Norwegian university. His correspondence with Grundtvig from 1813 is now regarded as a valuable source for Grundtvig’s view of Christianity at that time. In his diary entry for August 27th 1813 Pavels notes that Stenersen had proposed that the Society for the Wellbeing of Norway should use all its influence to get Grundtvig to Norway. In his proposition Stenersen asked who possessed such unity and purity of thought as to be able to understand fully the importance of scholarship; he himself had only one candidate - Grundtvig. From a contemporary standpoint he had won his way to the Christian faith. But the rationalist Pavels, the source of our information, was far from convinced that “no man in the whole of Norway” possessed these abilities in equal measure to Grundtvig”. He therefore had misgivings about “requesting him as Norway’s last and only deliverer”. When Grundtvig heard of Stenersen’s proposition he sought an audience with the King on September 8th at which he clearly expressed his desire to become Professor of History at the Norwegian University. Two Danish professors, Børge Thorlacius and Laurids Engelsto. found it strange, however, that Treschow, Sverdrup and Hersleb could “deify Grundtvig”. And his great wish was never fulfilled. Nonetheless he did not give up. On November 15th he saw that the post of curate was being advertised at Aggers church near Christiania and applied for the job. From his book Roskilde Rhymes (published on February 1st 1814) it is clear that he believed that it was there that his great work was to be accomplished. But in those very days Frederik VI was signing the peace of Kiel which would separate Norway from Denmark, and Grundtvig from his wish. In the preface to Danevirke (dated May 1817) he realised that he had deserved the scorn of the Norwegians, for he had expected too much of them. But he never forgot his Norwegian friends. He named one of his sons after Svend Hersleb, and another son married Stenersen’s daughter. When he himself visited Norway in 1851 he was welcomed like a prince.